Vascular endothelial growth factor in articular cartilage of healthy and osteoarthritic human knee joints. Issue 11 (1st November 2001) - Pfander, D; Körtje, D; Zimmermann, R; Weseloh, G; Kirsch, T; Gesslein, M; Cramer, T; Swoboda, B
Abstract : OBJECTIVE: To determine the levels of vascular endothelial growth factor (VEGF) mRNA and protein expression in normal and osteoarthritic (OA) human articular cartilage, and whether VEGF expression alters during the progression of OA. METHODS: Sections from normal and OA human knee cartilage were immunotained with a polyclonal antibody recognising VEGF. In addition, total RNA was isolated from normal and osteoarthritic human knee cartilage and analysed by reverse transcriptase-polymerase chain reaction (RT-PCR) for VEGF mRNA expression. RESULTS: VEGF was found to be present in normal and OA human knee cartilage in all cartilage layers. A significant increase of VEGF immunopositive chondrocytes to up to ∼82% was detected in severe OA cartilage compared with normal articular cartilage (∼56% of immunopositive chondrocytes). RT-PCR analysis showed the expression of VEGF also on the mRNA level. CONCLUSIONS: VEGF is expressed by articular chondrocytes in normal and OA human knee cartilage. The percentage of VEGF immunopositive chondrocytes significantly increases in late stages of the disease. The VEGF transcript levels encoding all four isoforms shows a big variability in samples from different donors, suggesting a distinct regulation of the expression of the four VEGF isoforms in normal and OA cartilage.